An organisational analysis of the implementation of telecare and telehealth: the whole systems demonstrator - Hendy Jane; Chrysanthaki Theopisti; Barlow James; Knapp Martin; Rogers Anne; Sanders Caroline; Bower Peter; Bowen Robert; Fitzpatrick Ray; Bardsley Martin; Newman Stanton (BMC, 2012)
Abstract Background To investigate organisational factors influencing the implementation challenges of redesigning services for people with long term conditions in three locations in England, using remote care (telehealth and telecare). Methods Case-studies of three sites forming the UK Department of Health's Whole Systems Demonstrator (WSD) Programme. Qualitative research techniques were used to obtain data from various sources, including semi-structured interviews, observation of meetings over the course programme and prior to its launch, and document review. Participants were managers and practitioners involved in the implementation of remote care services. Results The implementation of remote care was nested within a large pragmatic cluster randomised controlled trial (RCT), which formed a core element of the WSD programme. To produce robust benefits evidence, many aspect of the trial design could not be easily adapted to local circumstances. While remote care was successfully rolled-out, wider implementation lessons and levels of organisational learning across the sites were hindered by the requirements of the RCT. Conclusions The implementation of a complex innovation such as remote care requires it to organically evolve, be responsive and adaptable to the local health and social care system, driven by support from front-line staff and management. This need for evolution was not always aligned with the imperative to gather robust benefits evidence. This tension needs to be resolved if government ambitions for the evidence-based scaling-up of remote care are to be realised.